2021
DOI: 10.1097/md.0000000000027186
|View full text |Cite
|
Sign up to set email alerts
|

Factors behind the prevalence of carbapenem-resistant Klebsiella pneumoniae in pediatric wards

Abstract: The emergence of carbapenem-resistant Enterobacteriaceae made the treatment difficult, which has become a significant issue of public health. A sharp increase of carbapenem-resistance rate in Klebsiella pneumoniae was observed in a maternity and child health care hospital in Zunyi, China, in 2014. In 2015 to 2016, carbapenem-resistant Klebsiella pneumoniae (CRKp) isolated from all the clinical samples were analyzed to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The results of drug resistance genes showed that all 20 CRKP isolates carried carbapenem resistance genes, of which five isolates only carried bla KPC-2, six isolates only carried blaNDM-1, and the remaining nine isolates carried both carbapenem resistance genes. This indicated that carbapenemase production is the main drug resistance mechanism of CRKP in the hospital, consistent with reports in China [23,24]. The combined analysis of phenotypic drug resistance and the presence of drug resistance genes showed that the presence of aminoglycoside, quinolone, and sulfonamide drug resistance genes was not completely consistent with the results of phenotypic drug resistance analysis, and similar results were obtained in other studies [8,25].…”
Section: Discussionsupporting
confidence: 88%
“…The results of drug resistance genes showed that all 20 CRKP isolates carried carbapenem resistance genes, of which five isolates only carried bla KPC-2, six isolates only carried blaNDM-1, and the remaining nine isolates carried both carbapenem resistance genes. This indicated that carbapenemase production is the main drug resistance mechanism of CRKP in the hospital, consistent with reports in China [23,24]. The combined analysis of phenotypic drug resistance and the presence of drug resistance genes showed that the presence of aminoglycoside, quinolone, and sulfonamide drug resistance genes was not completely consistent with the results of phenotypic drug resistance analysis, and similar results were obtained in other studies [8,25].…”
Section: Discussionsupporting
confidence: 88%
“… 12 Research findings showed that nosocomial infection surveillance revealed an unexpectedly high rate of failure in neonatal units to meet hospital hygiene and hand hygiene requirements. 5 Bai et al found that nosocomial surveillance systems are needed to limit the spread of the infection caused by these pathogens resulting from the environmental exposure in NICUs. In the delivery room, neonatal intensive care unit (NICU), and the follow-up clinic, in collaboration with the interdisciplinary group, contact precautions and isolation procedures were instituted.…”
Section: Discussionmentioning
confidence: 99%
“…4 Due to the immature immune system of children, children are more susceptible to CRKP infection, and there are fewer antibiotics available for children than adults, and more complications occur in children, which brings great challenges to clinical treatment. 5 Therefore, there is a need to explore risk factors for CRKP in children to prevent antimicrobial resistance and consequently improve the prognosis. However, there are no scientific techniques or reliable methods to predict the prognosis of patients based on a single factor.…”
Section: Introductionmentioning
confidence: 99%
“…In China, KPC-2 is the predominant carbapenemase enzyme, succeeded by NDM and OXA types. 6 The predominant genotypes of CRKP in pediatric patients can vary significantly by region, 7,8 which contrasts with the more uniform profile observed in adult patients, where KPC-2 is the predominant enzyme. 9 In recent years, there has been a growing incidence of CRKP strains co-producing two or even three different carbapenemase enzymes.…”
Section: Introductionmentioning
confidence: 95%